Optimization of transfection of human coxsackie and adenovirus receptor into mammalian cells mediated by liposomes-base gene delivery - Baba, Sayang; Elengoe, Asita; Hussein, Abdul Rahim; Sugeng , Triwahyono; Draman, Samsul; Hamdan, Salehhuddin (Life Science Journal, 2015)
Cationic liposome-based reagents provide reliable and simple protocol for in vitro transfection in a broad range of mammalian cell types. High transfection efficacies and low cytotoxicity of a liposome-based transfection reagent was required to retain adequate viability and high level of transgene of transfected Chinese hamster ovary (CHO) cells for subsequent assay. Three commercial liposome-based transfection reagents were utilized and compared for their aptitude to transfect in-vitro CHO cells with reporter gene expressing the red fluorescent (pDsRed-N1) and fusion pDsRed-N1 plasmid containing human cDNA Coxsackie and Adenovirus Receptor (pCAR-DsRed). Xtreme HP Plasmid DNA transfection reagent (Roche) gave the highest transfection efficiencies compared to other tested reagents. The optimal Xtreme HP Plasmid DNA reagent had shown its higher transfection efficiency (39.25±1.00% MFI) and stable increment of DsRed-proportion cells with incubation period (24-72 hours), allowing sufficient yield and shortened the selection stably clone of successful transfected CHO-CARDsRed.